2018
DOI: 10.1177/0146167218783190
|View full text |Cite
|
Sign up to set email alerts
|

A Darker Side of Hope: Harmony-Focused Hope Decreases Collective Action Intentions Among the Disadvantaged

Abstract: Hope is viewed as a positive emotion associated with the motivation to change existing conditions. As such, it is highly relevant for social change, particularly when considering disadvantaged groups. We propose that, in the context of unequal intergroup relations, hope may actually undermine motivation for change among disadvantaged group members. Specifically, we distinguish between hope targeted at harmony with the outgroup and hope targeted at social equality between groups. Drawing on insights regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 34 publications
3
47
0
Order By: Relevance
“…Conversely, for Black queer youth with lower assimilation beliefs, high racial centrality was related to a lower orientation toward high‐risk activism than low racial centrality. This finding is in line with research of Palestinian citizens of Israel and Black Americans in the United States, which found that hope of integration with the dominant racial–ethnic group (Jewish citizens of Israel and White Americans) was negatively associated with intention to engage in collective action among marginalized group members with low collective identity (Hasan‐Aslih, Pliskin, van Zomeren, Halperin, & Saguy, ). One possible explanation is that Black queer youth who do not value integration with mainstream society but have a high sense of self as Black, do not see value in high‐risk activism.…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, for Black queer youth with lower assimilation beliefs, high racial centrality was related to a lower orientation toward high‐risk activism than low racial centrality. This finding is in line with research of Palestinian citizens of Israel and Black Americans in the United States, which found that hope of integration with the dominant racial–ethnic group (Jewish citizens of Israel and White Americans) was negatively associated with intention to engage in collective action among marginalized group members with low collective identity (Hasan‐Aslih, Pliskin, van Zomeren, Halperin, & Saguy, ). One possible explanation is that Black queer youth who do not value integration with mainstream society but have a high sense of self as Black, do not see value in high‐risk activism.…”
Section: Discussionsupporting
confidence: 88%
“…Whilst advantaged group allies seem to be effective in reducing discriminatory behaviours among perpetrators (e.g., Czopp & Monteith, 2003) or motivating others to act (see Roblain et al, 2020 this issue;Subašić et al, 2018), research on intergroup contact and collective action highlights the costs associated with their involvement from the perspective of the disadvantaged group. For instance, allies may put more emphasis on achieving harmonious intergroup relations, which can decrease disadvantaged group members' participation in collective action (Dixon et al, 2015;Hasan-Aslih et al, 2019), by reducing their anger and sense of efficacy, which are the classic predictors of collective action (Ufkes et al, 2016). The key goal of allyship is to assist disadvantaged groups in achieving their goals, thus it is crucial to understand how disadvantaged groups respond to allies' presence and involvement.…”
Section: Isadvantag Ed G Roup Per S Pec Tive On Allys Hipmentioning
confidence: 99%
“…Yet, other research found a positive effect of manipulated possibility on hope but not on collective action motivation, with its authors attributing a mere emotion‐coping role to hope (van Zomeren, Pauls, & Cohen‐Chen, ). Further, some hopes can also deflate collective action motivation, such as when the object of hope for disadvantaged groups is harmony between groups rather than equality (Hasan‐Aslih, Pliskin, van Zomeren, Halperin, & Saguy, ).…”
Section: Motivation By Expectancymentioning
confidence: 99%